Penetapan Lokasi Perumahan Kumuh oleh Pemerintah Daerah Kabupaten Badung Dengan Peraturan Daerah - I Kadek Dwi Melana Putra; I Nyoman Gede Sugiartha; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2022)
This study aims to analyze and describe the determination of the location of slum housing by the Regional Government of Badung Regency with Regional Regulations. Settlement is a space for humans which is also said to be a place to live for every human being. The growth that occurs in society often has positive and negative consequences. One of the problems that arise is the emergence of slum settlements. Based on the Regional Regulation, the categories of slum housing are listed based on the aspects contained in the housing, if there are aspects that are not appropriate, the Badung Regency local government will make efforts to evaluate and improve these aspects so that the housing can be declared livable housing. This regulation also aims to suppress the growth of slum housing so that it can become livable housing. Through this research, it is hoped that a good relationship between the local government and the community will be established in order to create livable housing that will have a good impact on the government and society.